BROWN BOOBY (SULA LEUCOGASTER) IN PERU: NEW RECORDS, HISTORICAL OCCURRENCE AND CURRENT STATUS - Gutiérrez, Ciprian (2017)
New records of the Brown Booby (Sula leucogaster) in Peru are documented in Guañape, Lobos de Afuera, Macabí and Mazorca islands, and Coles cape. In the fi rst locality, the individual observed corresponded to S. l. brewsteri, extending its dispersal range 3800 km south of its closest breeding area. In the other four areas, probably correspond to S. l. etesiaca, extending its range of dispersion 2860 km south of the closest reproduction area. Considering these observations and those published between 1972 and 2017, the species has been reported throughout the Peruvian coast between 3°S and 19°S, with a maximum of 50 individuals. Since 2008, the species it is reported almost every year, mostly during El Niño warm conditions, and to a lesser extent in normal and cold La Niña conditions, from casual observations to prolonged stays. Based on the observations presented here, the presence of the Brown Booby in Peru would be more common than has been considered previously in the literature, potentially being able to be considered as a regular visitor.